Novel 4-arylaminoquinazolines bearing N, N-diethyl(aminoethyl)amino moiety with antitumour activity as EGFRwt-TK inhibitor. (1st January 2019) - Zhang, Yaling; Chen, Li; Li, Xiabing; Gao, Li; Hao, Yunxia; Li, Baolin; Yan, Yaping
Abstract: Herein, four novel 4-arylaminoquinazoline derivatives with N, N -diethyl(aminoethyl)amino moiety were designed, synthesised and evaluated on biological activities in vitro . All synthesised compounds have inhibitory effects against tumour cells (SW480, A549, A431 and NCI-H1975). In particular, 4-(3-chloro-4-(3-fluorobenzyloxy)phenylamino)-6-(5-(( N, N -diethyl(aminoethyl))aminomethyl)furan-2-yl)quinazoline (6a ) and 6-(5-(( N, N -diethylethyl)aminomethyl)furan-2-yl)-4-(4-( E )-(propen-1-yl)phenylamino)quinazoline (6d ) were potent antitumour agents which showed high antiproliferative activities against tumour cells in vitro . Moreover, compound 6a could induce late apoptosis of A549 cells at high concentrations and arrest cell cycle of A549 cells in the G0/G1 phase at tested concentrations. Also, compound 6a could inhibit the activity of wild type epidermal growth factor receptor tyrosine kinase (EGFR wt -TK) with IC50 value of 15.60 nM. Molecular docking showed that compound 6a formed three hydrogen bonds with EGFR wt -TK, while lapatinib formed only two hydrogen bonds with the receptor protein. It is believed that this work would be giving a reference for developing anti-cancer drugs targeted EGFR-TK. Graphical Abstract: